Modeling of resonant-tunneling diode with “Quant ST” - Fedyay, Artem; Moskaliuk, Volodymyr (Видавництво Львівської політехніки, 2012)
Two-valley numerical model of resonant tunneling diode (RTD) is developed. Coherent and incoherent channels of electron transport and transport through emitter quantum well(EQW) are taken into account. Visualization of the micro- and macroscopic quantities was done, using “QuanT ST” application, developed by the authors and based upon the model.
Keywords: quantum transport; resonant-tunneling diode; quantitative simulation; Quant ST